Microbial succession and its effect on the formation of umami peptides during sufu fermentation - Mao, Jieqi; Zhou, Zhilei; Yang, Hongshun (Frontiers in Microbiology, 2023)
Sufu, a traditional Chinese fermented food, is famous for its unique umami flavor. This study investigated the dynamic change of both umami peptides and microbial communities during sufu production. Based on peptidomic analysis, 9081 key peptides mainly involved in amino acid transport and metabolism, peptidase activity and hydrolase activity were identified. After that, twenty-six high-quality umami peptides with ascending trend were distinguished by Fuzzy c-means clustering. Then, through correlation analysis, five bacterial species (Enterococcus italicus, Leuconostoc citreum, L. mesenteroides, L. pseudomesenteroides, Tetragenococcus halophilus) and two fungi species (Cladosporium colombiae, Hannaella oryzae) were identified to be the core functional microorganisms for formation of umami peptides. Functional annotation of five lactic acid bacteria indicated their important functions to be carbohydrate metabolism, amino acid metabolism and nucleotide metabolism, which proved their umami peptides production ability. Overall, this study enhanced our understanding of microbial communities and the formation mechanism of umami peptides in sufu , and provide novel insights for quality control and flavor improvement of tofu products.